2003
DOI: 10.1103/physrevb.68.045103
|View full text |Cite
|
Sign up to set email alerts
|

Role of occupieddbands in the dynamics of excited electrons and holes in Ag

Abstract: The role that occupied d bands play in the inelastic lifetime of bulk and surface states in Ag is investigated from the knowledge of the quasiparticle self-energy. In the case of bulk electrons, sp bands are taken to be free-electron like. For surface states, the surface band structure of sp states is described with the use of a realistic one-dimensional hamiltonian. The presence of occupied d states is considered in both cases by introducing a polarizable background. We obtain inelastic lifetimes of bulk elec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 54 publications
4
34
0
Order By: Relevance
“…(2)], which contains contributions from bulk, surface, and image-potential states. It was shown 43,54 that ImW decays when moving away from the surface to vacuum. Since rare-gas spacer layers push the image-potential state electron into the vacuum, the intraband scattering rate decreases through the decrease of ImW .…”
Section: B Rare-gas Covered Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…(2)], which contains contributions from bulk, surface, and image-potential states. It was shown 43,54 that ImW decays when moving away from the surface to vacuum. Since rare-gas spacer layers push the image-potential state electron into the vacuum, the intraband scattering rate decreases through the decrease of ImW .…”
Section: B Rare-gas Covered Surfacesmentioning
confidence: 99%
“…Although this opens a further inelastic decay channel for electrons in the image-potential states, it has been shown that the highly nonlocal character of the self-energy near the surface leads astonishingly to an increase of their lifetime at the point of silver surfaces. 42,43 A priori the surface plasmon excitation channel on silver is also expected to play an important role for k = 0.…”
Section: A Clean Cu and Ag Surfacesmentioning
confidence: 99%
“…An extension of the s-d-polarization model first proposed by Liebsch [77] for a jellium model to the model potential described above (see Section 2.2) [45] has been made recently by López-Bastidas et al [78] and García-Lekue et al [75,79]. In this case, the electron states are taken to be described by the eigenvalues and eigenfunctions of the model Hamiltonian and this bounded assembly of electrons is then immersed in a polarizable background of d-electrons which extends from deep into the solid up to a certain plane z ¼ z d .…”
Section: D-screening In a Bounded Electron Gasmentioning
confidence: 99%
“…0Þ for Ag, Au and Cu are 4, 6.6 and 5.6, respectively [52,75]. García-Lekue et al [75] have analyzed the impact of d-electron screening and concluded that, in the long-wavelength limit (q ! 0) the increase of the lifetimes is negligible.…”
Section: D-screening In a Homogeneous Electron Gasmentioning
confidence: 99%
See 1 more Smart Citation